2017
DOI: 10.3201/eid2311.171071
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila Serogroup 1 in the Water Facilities of a Tertiary Healthcare Center, India

Abstract: Proactive environmental surveillance for Legionella pneumophila in hospitals that treat immunocompromised patients is a useful strategy for preventing nosocomial Legionnaires’ disease. We report the presence of L. pneumophila serogroup 1 in 15.2% of the water systems of our tertiary healthcare center, which should prompt health officials to formulate mitigation policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…37 In previous studies, we reported Legionella colonization in the hospital water supply. 31,32 The results of our environmental study increased the index of suspicion for nosocomial LD among clinicians and recommended Legionella diagnostic testing for suspected cases of nosocomial pneumonia. According to the CDC, Legionella testing in patients at risk for LD with nosocomial pneumonia should always be pursued; however, environmental cultures should be reserved for clearly documented cases of HALD.…”
Section: Study Populationmentioning
confidence: 86%
See 1 more Smart Citation
“…37 In previous studies, we reported Legionella colonization in the hospital water supply. 31,32 The results of our environmental study increased the index of suspicion for nosocomial LD among clinicians and recommended Legionella diagnostic testing for suspected cases of nosocomial pneumonia. According to the CDC, Legionella testing in patients at risk for LD with nosocomial pneumonia should always be pursued; however, environmental cultures should be reserved for clearly documented cases of HALD.…”
Section: Study Populationmentioning
confidence: 86%
“…However, in environmental surveys, non-Lp1 serogroups were also recovered from hospital water samples. 31,32 Continuous clinical surveillance is required to identify the significance of these serotypes in LD patients.…”
Section: Study Populationmentioning
confidence: 99%
“…12 In India, L. pneumophila was found in 6.66 to 15.2% of distal outlet waters in patient care areas in tertiary hospitals. 13 14 Outbreaks of the LD are more common in late summer and early autumn because of stagnation of water which provides an ideal ground for bacterial growth. 15…”
Section: Reservoirsmentioning
confidence: 99%
“…Legionella isolation and identification from water samples was done following the guidelines issued by the US Centers for Disease Control and Prevention (19). The detailed methodology regarding L. pneumophila environmental surveillance has been published elsewhere (20,21).…”
Section: Environmental Surveillancementioning
confidence: 99%